Zinc-induced enhancement in growth, ionic contents and yield of bio-fortified and standard wheat (Triticum aestivum L.) varieties - Sibgha Noreen; Maham Sultan; Seema Mahmood; Kausar Hussain Shah; Muhammad Salim Akhter; Zafar-Ullah Zafar; Maqsooda Parveen; Chukwuma C. Ogbaga (International Journal of Applied and Experimental Biology)
Zinc as a micronutrient is highly essential for animals and plants to attain optimum growth and development. Zinc-deficient soils result in stunted and abnormal growth of plants. Three wheat varieties, i.e., Zincol-2016 (biofortified), Galaxy-2013, and Punjab-2011 (both non-biofortified), were sown in pots containing fertile soil in a completely randomized design with four replicas. The seedlings were sprayed with four zinc solutions (Control, 0.03%, 0.06%, and 0.09% of Zn as ZnSO4.7H2O) 40 days after sowing. It was observed that the impact of 0.06% zinc spray was more pronounced on wheat plants as compared to that of 0.03% and 0.09%. More pronounced improvement in growth, chlorophyll content, total soluble proteins, and sugars was observed in cv. Zincol-2016 as compared to that in the other two varieties, Galaxy-2013 and Punjab-2011. Similarly, Zn foliar spray significantly enhanced root, straw, and grain K+, Cu2+, Zn2+, and Fe2+ contents in all three cultivars. In contrast, grain phytate contents were reduced with increased supplementation of Zn. Data revealed that grain yield was improved significantly by exogenous application of zinc, especially at 0.06% in all three wheat varieties, but being more promising in Zincol-2016. Furthermore, Zincol-2016 accumulated higher zinc contents in grains as compared to that in Galaxy-2013 and Punjab-2011. Foliar application of zinc resulted in higher uptake and accumulation of this element from soil to seeds, thereby resulting in improved vegetative growth.